Development and optimization of a moving-magnet tubular linear permanent magnet motor for use in a reciprocating compressor of household refrigerators - Abdalla, I.I. (Elsevier Ltd, 2016)
This paper presents the development, validation and design optimization of a moving-magnet tubular linear permanent magnet motor (TLPMM) with a trapezoidal permanent magnet shape. The design optimization was implemented by a two-dimensional Finite-Element Analysis (2-D FEA) and the validation was established by using Matlab software. The proposed motor has been designed to produce 85 W output power which is enough to operate the reciprocating compressor of a household refrigerator system. The purpose of the optimization is to achieve a maximum efficiency and minimum losses, where the angle of PMs, split-ratio and Tmr/Tp after optimized, the motor produced the highest efficiency by 93.8. Â© 2015 Elsevier Ltd. All rights reserved.